A Survey on Iris Recognition System - Kumar, Prabhat; Ahirwar, Manish; Deen, Anjna (International Journal of Computer Sciences and Engineering, 2019)
Biometric identification makes utilization of physical and behavioral traits to recognize an individual. It really is currently a measurable physical feature which is believed far very much reliable and safer than passwords. It authenticates secure access and helps in gaining access to data through fingerprints or DNA which are the biological information of human beings. Many biometric systems have recently been developed and so are being utilized to authenticate the individual identity. Iris recognition systems are being used broadly and have became efficient at individual recognition with high precision and practically perfect coordination. The features extracted from iris of both eye of the same person varies, this helps it to be more secured method of authentication in comparison to other biometric systems. This paper offers a review of different methods and algorithms utilized by different experts and their undertake performance of iris recognition system along with identification of gap for potential work.